The Influence of Various Types of Bracing on Force Distribution in Braced Barrel Vaults - Chrust, Jędrzej; Chybiński, Marcin; Garasz, Piotr; Kurzawa, Zdzisław; Piórecki, Wojciech; Polus, Łukasz; Stajkowska, Weronika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this paper the authors analysed four single-layered braced barrel vaults with different types of bracing. Each braced barrel vault covered the area of 20 m x 28 m and was made from steel hollow sections. The static-strength analyses of the structures were conducted using the Autodesk Robot Structural Analysis program, taking into account self-weight, glass cover, snow load and wind load. In the case of wind load, wind pressure perpendicular to the longitudinal wall was determined in accordance with the EN 1991-1-4 standard.
Keywords: barrel vault; bracing; large span structures; steel structures; sklepienie kolebkowe; konstrukcje o dużych rozpiętościach; konstrukcje stalowe